Современный литоморфогенез на восточно-арктическом шельфе России: монография - Дударев О. В. Олег Викторович; Чаркин А. Н. Александр Николаевич; Шахова Н. Е. Наталья Евгеньевна; Мазуров А. К. Алексей Карпович; Семилетов И. П. Игорь Петрович (Томск, Изд-то ТПУ, 2016)
Заглавие с титульного экрана